Computational Investigations on Phycocyanobilin - Matteo Gigli; Matteo Donati; Massimo Sgarzi; Marco Bortoluzzi (Chemistry Proceedings)
Phycocyanobilin was computationally investigated by means of DFT calculations in combination with implicit solvation starting from X-ray data. Different conformations and degrees of protonation were considered, and the acidity constants were estimated. The computed data suggest a syn-syn-syn conformation for the molecule, with the two carboxylic groups deprotonated under physiological conditions and weak acidic behavior of one of the pyrrolone heterocycles. The absorption transitions in the visible range were studied by means of TD-DFT calculations, focusing on the molecular orbitals involved. The frontier orbitals have a dominant role in the lowest energy absorption.